2012
DOI: 10.3233/jad-2012-120079
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Volume and Cognition in a Randomized Trial of Exercise and Social Interaction in a Community-Based Sample of Non-Demented Chinese Elders

Abstract: Physical exercise has been shown to increase brain volume and improve cognition in randomized trials of non-demented elderly. Although greater social engagement was found to reduce dementia risk in observational studies, randomized trials of social interventions have not been reported. A representative sample of 120 elderly from Shanghai, China was randomized to four groups (Tai Chi, Walking, Social Interaction, No Intervention) for 40 weeks. Two MRIs were obtained, one before the intervention period, the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
263
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(279 citation statements)
references
References 40 publications
9
263
2
5
Order By: Relevance
“…Of note, one of these studies including a long-term follow-up reported sustained Tai Chi-related improvements in executive function at 1 year (i.e., 8 months post intervention). 29 In addition, measures of learning and memory and semantic fluency (AVLT, CVLT, categories) also improved with Tai Chi in the three higher quality RCTs; 23,26,29 in one study these improvements were greater relative to aerobic exercise. 26 One study also reported improvements in overall global cognitive function (Mattis DRS) and total brain volume assessed via MRI.…”
Section: Synthesis Of Studies Of Cognitively Healthy Adultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Of note, one of these studies including a long-term follow-up reported sustained Tai Chi-related improvements in executive function at 1 year (i.e., 8 months post intervention). 29 In addition, measures of learning and memory and semantic fluency (AVLT, CVLT, categories) also improved with Tai Chi in the three higher quality RCTs; 23,26,29 in one study these improvements were greater relative to aerobic exercise. 26 One study also reported improvements in overall global cognitive function (Mattis DRS) and total brain volume assessed via MRI.…”
Section: Synthesis Of Studies Of Cognitively Healthy Adultsmentioning
confidence: 92%
“…After excluding the one study with a low quality score indicating bias, 27 the effect size was reduced but remained statistically significant and indicated no heterogeneity between studies (Hedge's g=0.394; p=0.004 I 2 =0%). Meta-analyses of the two studies 26,29 that compared Tai Chi to another exercise intervention (walking and "western exercise") also showed a modest positive effect size (Hedge's g=0.509; p=0.003, I 2 =0%; Figure 2b). Of note, one of these studies including a long-term follow-up reported sustained Tai Chi-related improvements in executive function at 1 year (i.e., 8 months post intervention).…”
Section: Synthesis Of Studies Of Cognitively Healthy Adultsmentioning
confidence: 92%
See 3 more Smart Citations